2008
DOI: 10.1016/j.cellbi.2007.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone receptors in carpal tunnel syndrome

Abstract: Carpal tunnel syndrome (CTS) is a compression median nerve neuropathy common in women at menopausal age. The aim of this work was to study immunohistochemically the expression of estrogen (ER) and progesterone (PR) receptors in CTS and control specimens. Biopsies of transverse carpal ligament (TCL) and flexor tendon synovitis were collected from 23 women and from 7 men undergoing surgery for median nerve decompression at the wrist for CTS. In TCL and synovial tissue, cells expressed ER and PR with statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…Toesca et al4 evaluated the ER and PR expression in the specimens obtained from 30 CTS cases and four controls. Both TCL and synovial tissue from CTS patients expressed ERα, but PR was observed only in TCL samples and its appearance decreased with age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Toesca et al4 evaluated the ER and PR expression in the specimens obtained from 30 CTS cases and four controls. Both TCL and synovial tissue from CTS patients expressed ERα, but PR was observed only in TCL samples and its appearance decreased with age.…”
Section: Discussionmentioning
confidence: 99%
“…The number of ER- and PR-positive cells in non-CTS patients was significantly lower than that in CTS patients. Authors suggested that localization of the ER and PR proteins in the normal TCL is related to the theory that female sex hormones influence the physiological modulation of TCL metabolism 4. These receptors have already been supposed to have an effect on the structure of the ligaments in studies on human anterior cruciate ligament 15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implicates these receptors and potentially oestrogen and progesterone in the pathogenesis of carpal tunnel syndrome. Interestingly, the number of ER positive cells in the transverse carpal ligament and synovial tissue increased with age to a peak at 55-70, decreasing thereafter [36].…”
Section: Role Of Oestrogenmentioning
confidence: 99%